2019
DOI: 10.1177/1350506819893728
|View full text |Cite
|
Sign up to set email alerts
|

Induced abortion and gender (in)equality in Europe: A panel analysis

Abstract: Induced abortion is a worldwide practice and its legalisation is a persistent demand of the women’s movement. Although in the academic literature there are numerous studies that address the study of fertility, nowhere near as much attention has been given to the analysis of induced abortion and its determining factors, and even less to the consideration of gender equality as a variable through which to understand it. This article focuses on the influence of gender equality on the rate of induced abortion in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“… 30 Recent research has shown that higher gender equality at the country level is associated with a lower frequency of abortion. 31 Here, we propose to use macro-level indices of gender equality to expose the association (or its absence) between MA ratios and gender equality in Europe, hypothesising that more gender-equal countries will have higher MA ratios.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Recent research has shown that higher gender equality at the country level is associated with a lower frequency of abortion. 31 Here, we propose to use macro-level indices of gender equality to expose the association (or its absence) between MA ratios and gender equality in Europe, hypothesising that more gender-equal countries will have higher MA ratios.…”
Section: Introductionmentioning
confidence: 99%